2017
DOI: 10.4103/1119-3077.180066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a combined approach for the esthetic management of fluorosed teeth: Three-year results

Abstract: Fluorosed teeth revealed significantly better esthetic appearance after microabrasion and combined therapy and at 3-year follow-up compared to those at baseline (P P Conclusions: The combined therapy was effective in the esthetic management of fluorosed teeth. However, a significant relapse was observed in the esthetic appearance and brown stains of these patients after 3 years, which also reduced patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Literature search did not show any evidence on objective evaluation of interim or long-term clinical color stability results for at-home bleaching combined with resin infiltration and microabrasion for management of stained fluorotic teeth. One report by Celik et al was a three-year posttreatment subjective evaluation for the stability of the color change achieved with enamel microabrasion and at-home bleaching (10% carbamide peroxide, Opalescence, Ultadent Inc, UT, United States) for fluorotic teeth [21]. It was concluded that there was significant relapse in esthetic improvement and brown stains recurrence [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature search did not show any evidence on objective evaluation of interim or long-term clinical color stability results for at-home bleaching combined with resin infiltration and microabrasion for management of stained fluorotic teeth. One report by Celik et al was a three-year posttreatment subjective evaluation for the stability of the color change achieved with enamel microabrasion and at-home bleaching (10% carbamide peroxide, Opalescence, Ultadent Inc, UT, United States) for fluorotic teeth [21]. It was concluded that there was significant relapse in esthetic improvement and brown stains recurrence [21].…”
Section: Discussionmentioning
confidence: 99%
“…One report by Celik et al was a three-year posttreatment subjective evaluation for the stability of the color change achieved with enamel microabrasion and at-home bleaching (10% carbamide peroxide, Opalescence, Ultadent Inc, UT, United States) for fluorotic teeth [21]. It was concluded that there was significant relapse in esthetic improvement and brown stains recurrence [21]. Some of the cases in the present report are part of the clinical trial aimed to assess the long-term objective assessment of color stability achieved with at-home bleaching combined with microabrasion and resin infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Some disadvantages of microabrasion include difficulties in the complete elimination of deep white opaque area and brown stain from the tooth, slightly yellowish color of enamel after treatment, and uniformity of the tooth appearance is disrupted. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Dental changes caused by fluorosis generate mild to severe esthetic problems 5 . Depending on the severity of the damage, it could impact patients' quality of life and psychosocial aspects related to esthetics 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its lower molecular weight, HP can reach the pulp cavity, causing tooth sensitivity 16,17 . Therefore, changes caused in the enamel due to MA can be expected to increase the amount of HP inside the pulp chamber, 16,18,19 thus increasing tooth sensitivity (TS) 5,13,15 …”
Section: Introductionmentioning
confidence: 99%